2017
DOI: 10.1093/gji/ggx276
|View full text |Cite
|
Sign up to set email alerts
|

Integration of SH seismic reflection and Love-wave dispersion data for shear wave velocity determination over quick clays

Abstract: Quick clay is a water-saturated formation originally formed through flocculation and deposition in a marine to brackish environment. It is subsequently leached to low salinity by freshwater flow. If its strength decreases, then the flocculated structure collapses leading to landslides of varying destructiveness. Leaching can result in a reduction of the undisturbed shear strength of these clays and suggestions exist that a reduction in shear wave velocities is also possible. Integration of SH seismic reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, the VP/VS values are extremely high in the edges of the profile with values above 20, which seem unrealistic and not representative for saturated clays and sands. The high values of VP/VS in these positions may be related to a lower resolution of the VS and VP models in these areas and/or due to extremely low VS (studies in the same area,Polom et al 2013 andComina et al 2017, obtained similar values) Bailey et al (2013). associate high VP/VS to an increased porosity, saturation and clay content, all of which are conditions present in this study area.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…However, the VP/VS values are extremely high in the edges of the profile with values above 20, which seem unrealistic and not representative for saturated clays and sands. The high values of VP/VS in these positions may be related to a lower resolution of the VS and VP models in these areas and/or due to extremely low VS (studies in the same area,Polom et al 2013 andComina et al 2017, obtained similar values) Bailey et al (2013). associate high VP/VS to an increased porosity, saturation and clay content, all of which are conditions present in this study area.…”
mentioning
confidence: 53%
“…They have extensively been studied by geotechnical and resistivity methods (Dahlin et al 2013;Löfroth et al 2011;Lundström, Larsson and Dahlin 2009;Solberg et al 2012Solberg et al , 2016Wang, Malehmir and Bastani 2016), while only a few studies report the usage of surface-wave dispersion analysis for different investigations on quick clays (e.g. Comina et al 2017;Donohue et al 2012;Long, Wood and L'Heureux 2017;Sauvin et al 2013). Some of the most recent works on quick clays (leached clays) revealed that these materials cannot be distinguished from unleached clays using only shear-wave velocity (VS) measurements (Long et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the objective of contributing to characterize and understand the seismoelectric method when applied to glacial environments, we present in this work an analytic study of the electromagnetic responses to pure shear horizontal (SH) seismic waves, generated by a shearing force acting at the top of a glacier overlying a rocky substratum. Concerning the choice of the source, on the one hand, we have proved in a previous work (Zyserman et al, 2017a) that the signal-to-noise ratio can be higher in this case than when using compressional sources, and on the other hand, although up to now this kind of sources has not been used in seismoelectric field studies, they have been employed successfully in several works aiming to characterize the shallow subsurface (Beilecke et al, 2016;Comina et al, 2017;Konstantaki et al, 2013;Konstantaki et al, 2015;Prior et al, 2017;Stucchi et al, 2017). The ice forming the glacier is treated as an elastic medium; this is a common assumption when performing seismic studies (Collins et al, 2016;Podolskiy & Fabian, 2016;Presnov et al, 2014b;Presnov et al, 2014a).…”
Section: Research Articlementioning
confidence: 99%
“…Quite recently, Beilecke et al (2016) carried out high resolution, near surface, shear wave reflection seismic measurements to investigate the fault structure in a CO 2 deposition site in Australia. We mention, finally, the works of Stucchi et al (2017) and Comina et al (2017), integrating SH-wave measurements with P wave and Love-wave, respectively, to investigate different geological systems to assess landslide risks. The mentioned works show that there is evidence of successful usage of SH waves to investigate the subsoil.…”
mentioning
confidence: 99%